Interactive effect of supervisory styles and careerist orientation on enhancing creativity - Ganesh Bhattarai; Dipendra Karki; Bharat Rai; Prem Bahadur Budhathoki (Cogent Business & Management, 2024)
This study addresses a crucial theoretical gap by investigating how supervisors' supervisory styles and subordinates' careerist orientation jointly influence subordinate creativity. It examines the direct impact of two supervisor styles—supportive and noncontrolling supervision—on subordinates' creativity and the moderating role of careerist orientation. Data were collected via surveys from nonprofit Nepalese NGOs, resulting in 499 responses. The study used AMOS for data purification and hierarchical regression for hypothesis testing by employing positivist methodology and deductive reasoning. Results reveal that supportive behavior positively impacts subordinates' creativity, while noncontrolling supervision has a negative impact. Moreover, the study uncovers nuanced differences: supportive supervision positively affects creativity for individuals with low career orientation; however, this effect diminishes for those with high career orientation. Similarly, the positive impact of noncontrolling supervision on creativity is pronounced for low career orientation employees, but it turns harmful for high career orientation individuals. These findings hold implications for theoretical understanding and practical implementation, offering insights into the complex interplay between supervisory styles, careerist orientation, and creativity. The study contributes to future research directions and managerial strategies for fostering creativity.
Keywords: L20; L25; L30; M12; 650; Creativity; careerism; nepalese evidence; controlling supervision; noncontrolling supervision